PENGARUH PENDIDIKAN KEWARGANEGARAAN DALAM MEMBENTUK KEPRIBADIAN TARUNA PROGRAM STUDI TELEKOMUNIKASI DAN NAVIGASI UDARA (TNU) SEKOLAH TINGGI PENERBANGAN INDONESIA(STPI) CURUG – TANGERANG - Pribadi Asih (Politeknik Penerbangan Indonesia Curug)
This study ains to analyze and determine(1) Kewarganegaraan (Civics) 2) Kepribadian (Building nation Characters) The method used in this study is a survey method, with a population of 150 people. This is used to examine the research hypotheses by means of multivariate statiscal multiple linear regision using SPSS.20. The result obtained are : (1) The existence of a positive and significant effect of Civics on building nation characters Civics,. Civics can improve atitude, Civics will be able to improve building Nation Characters